Tuning the Geometrical Structure by Doping the Silicon Clusters - P. Gruene; A. Fielicke; G. Meijer; E. Janssens; V. T. Ngan; M. T. Nguyen; P. Lievens (My University, 2008)
Tuning the Geometrical Structure by Doping the Silicon Clusters
Keywords: Silicon clusters